Cognitive Effects of Social Media Use: A Case of Older Adults. (July 2018) - Quinn, Kelly
Research on the effects of social media use at older ages has largely focused on social benefits. Yet, participation in these new media forms may result in other favorable outcomes, such as improved cognitive functioning. Using a wait list-control design, this study examines the effects of social media engagement among novice adult social media users, aged 65 and older, in four cognitive domains: attention, processing speed, working memory, and inhibitory control. Baseline and multiple post-tests indicate improvement of intervention participants in inhibitory control. These findings demonstrate that the benefits of social media use at older ages extend beyond mere social engagement, and into other domains of everyday well-being.